Let the Students Speak: Essays on Pediatrics and Vision Therapy from Southern College of Optometry 4th Years. - Cook, Mallory; Overland, Amy; Trainer, Kristen; Kota, Madhurima (Optometry & Visual Performance, 2025)
Almost 15 years ago, the Glen Steele and Al Fors Scholarship was created at Southern College of Optometry. It honors two Professors Emeriti who taught several generations of SCO students in the areas of pediatrics and vision therapy. The college prides itself on keeping student debt as low as possible, and one of the ways it does so is through scholarships. As part of this scholarship, the 4th year students are asked to write an essay on vision. We keep the instructions vague, as we want to see where the students take the essay. This year's crop of essays covered a variety of topics, and with the students' permission, we wanted to share their most excellent essays over the next two issues. Hopefully their visions give you pause and allow you to reflect on your model of vision.